1999
DOI: 10.1046/j.1469-8137.1999.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble and membrane‐associated nitrate reductases in the dinoflagellate Peridinium gatunense

Abstract: An improved method of cell fractionation allowed the extraction of soluble (sNR) and membrane-associated (mNR) forms of nitrate reductase (NR) from a dinoflagellate, even though in previous studies only mNR had been found in these algae. Both activities were assayed in cell-free extracts of Peridinium gatunense from Lake Kinneret, Israel, after disruption of the cells and differential centrifugation. In the cultures used, sNR showed much higher NO $ − -reducing activity. Only a low proportion, 2n5-3% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…Shukla & Kashyap 1999) and dinoflagellates (Kristiansen 1983, Witt et al 1999. Temperature responses of NR are also similar: Witt et al (1999) found E a values for NR from Peridinium gatunense of 23 to 29 kJ mol -1 ; Kristiansen (1983), derived an E a of 38 kJ mol -1 for NR from Heterocapsa triqueta; and Gao et al (1993) calculated an E a of 36.5 kJ mol -1 for NR from Skeletonema costatum, all very similar to the overall value found in the present study.…”
Section: Temperature Effects On Nitrate Metabolismsupporting
confidence: 74%
“…Shukla & Kashyap 1999) and dinoflagellates (Kristiansen 1983, Witt et al 1999. Temperature responses of NR are also similar: Witt et al (1999) found E a values for NR from Peridinium gatunense of 23 to 29 kJ mol -1 ; Kristiansen (1983), derived an E a of 38 kJ mol -1 for NR from Heterocapsa triqueta; and Gao et al (1993) calculated an E a of 36.5 kJ mol -1 for NR from Skeletonema costatum, all very similar to the overall value found in the present study.…”
Section: Temperature Effects On Nitrate Metabolismsupporting
confidence: 74%
“…Enhanced Fe reduction as a result of nitrate reductase activity was reported for Fedeplete marine diatom (24). Nevertheless, Fe-deplete P. gatunense, grown on nitrate or ammonia, reduce FeEDTA to the same extent (Table 2), as expected by the low membranebound nitrate reductase activity of P. gatunense (41).…”
Section: Iron(iii) Reduction By Laboratory Culturessupporting
confidence: 52%
“…Ceratium hirundinella was collected in higher numbers near a river inflow with higher NO 3 and PO 4 than the main reservoir (Kawabata and Kagawa, 1988). The mechanism explaining the effect of nitrates on blooms may be a low affinity for nitrate by nitrate reductase, which allows the dinoflagellate to outcompete other algae (Witt et al, 1999 for Peridinium gatunense). A decrease in N:P due to an increase in total phosphorus (TP) attributed to a wastewater treatment plant, caused a bloom of Ceratium hirundinella in Albert Falls Reservoir .…”
Section: A Dinoflagellate Bloomsmentioning
confidence: 99%